The Influence of Dedi Mulyadi’s Populist Leadership Content on Civic Disposition - Isyeu Nur Cahyani; Cecep Darmawan; Leni Anggraeni (Universitas Lambung Mangkurat, 2026)
Social media has become a central arena for political communication in the digital era, particularly in constructing leadership images, disseminating political messages, and fostering perceived closeness with the public. Populist leadership content distributed through digital platforms is typically characterized by personal, emotional, and cultural narratives, which have the potential to shape how young people think, behave, and perceive social reality as citizens. In this context, the populist leadership content of Dedi Mulyadi is noteworthy, as it consistently emphasizes proximity to the community, moral storytelling, and the use of strong local cultural symbols, especially those rooted in Sundanese identity. Such strategies are considered effective in building emotional bonds with audiences, particularly students. However, this populist approach also raises concerns, as it may prioritize emotional mobilization over the cultivation of reflective and substantive civic values.This study aims to analyze the influence of Dedi Mulyadi’s populist leadership content on the formation of civic disposition among students of the Faculty of Social Sciences Education (FPIPS), Universitas Pendidikan Indonesia. Specifically, it examines students’ perceptions of mediated intimacy, analyzes the effects of digital directness and performative authenticity on civic disposition, and formulates solutions to address the dominance of emotional appeals in populist content. Employing a quantitative correlational design with a survey method, the findings reveal a significant influence of populist leadership content on students’ civic disposition, indicated by a t-value of 3.702 (p < 0.05). Furthermore, a positive correlation is identified (r = 0.362), suggesting a weak but meaningful relationship. Overall, leadership content that highlights social closeness, public problem-solving, and moral narratives contributes to shaping students’ civic attitudes, while also underscoring the need to strengthen critical.